2013
DOI: 10.1017/jfm.2013.502
|View full text |Cite
|
Sign up to set email alerts
|

Weakly nonlinear instability of planar viscous sheets

Abstract: A second-order instability analysis has been performed for sinuous disturbances on two-dimensional planar viscous sheets moving in a stationary gas medium using a perturbation technique. The solutions of second-order interface disturbances have been derived for both temporal instability and spatial instability. It has been found that the second-order interface deformation of the fundamental sinuous wave is varicose or dilational, causing disintegration and resulting in ligaments which are interspaced by half a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…By including the viscous stresses in the liquid, the model complements the results of Yuen [1] for the inviscid case and Yang and co-authors [2] for a plane viscous liquid sheet. In a weakly nonlinear analysis, velocity, pressure and jet surface shape are expanded in series with respect to a small deformation parameter, here the initial amplitude of the jet deformation, yielding a set of equations with different powers of the parameter.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…By including the viscous stresses in the liquid, the model complements the results of Yuen [1] for the inviscid case and Yang and co-authors [2] for a plane viscous liquid sheet. In a weakly nonlinear analysis, velocity, pressure and jet surface shape are expanded in series with respect to a small deformation parameter, here the initial amplitude of the jet deformation, yielding a set of equations with different powers of the parameter.…”
Section: Discussionmentioning
confidence: 56%
“…sheet stability [2]. In a 2016 ILASS paper [3], the jet geometry was considered by the present authors, introducing the need for a polynomial approximation of one part of the viscous contribution, that could not be fully solved analytically, due to the presence of Bessel function products with different arguments.…”
mentioning
confidence: 99%
“…Early nonlinear studies on the capillary instability of inviscid liquid jets were carried up to the third order contributions to the jet deformation and showed the nonlinear interaction between different modes. A recent study on the weakly nonlinear instability of planar Newtonian liquid sheets revealed the role of the liquid viscosity in the sheet stability behavior and showed a complicated influence [1]. Here, the instability of a liquid jet is examined as the axisymmetric counterpart of the sheet, in search for corresponding insight into the role of the liquid viscosity in the jet instability mechanism.…”
mentioning
confidence: 99%
“…The asymptotic analytical perturbation solution for weakly nonlinear instability of the linear sinuous mode was investigated in the study of Clark & Dombrowski (1972), Jazayeri & Li (2000) and Yang et al (2013). It was found that the first harmonic of the linear sinuous mode is varicose, which explains the disintegration of sinuous waves.…”
mentioning
confidence: 99%
“…In the theoretical analysis of Squire (1953), Clark & Dombrowski (1972), Asare, Takahashi & Hoffman (1981), Jazayeri & Li (2000) and Yang et al (2013), only the linear sinuous mode was investigated, and in the experiments of Squire (1953), Hagerty & Shea (1955), Crapper, Dombrowski & Pyott (1975), Asare et al (1981) and Tammisola et al (2011), the waves were evidently characterized by sinuous characters. However, Mitra, Li & Renksizbulut (2001) offered a different opinion.…”
mentioning
confidence: 99%